Fiction Series for Teenagers: A Coeducational View - Gil Tévar, Simón; Gil Quintana, Javier; Hueso Romero, José Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Currently, there is a boom in coeducational fiction series, primarily aimed at adolescent audiences. In this regard, the aim is to analyze university students' and interviews perceptions of coeducation, as well as to analyze and explore the coeducational potential of the selected fiction series in depth. This research adopts a mixed approach, analyzing 191 questionnaires (quantitative) and 11 semi-structured (qualitative). The study reflects a generation critical of discriminatory representations, identifying relevant aspects of coeducation in audiovisual.